Comparative study on microbial enhanced oil recovery using mannosylerithritol lipids and surfactin - José de Andrade, Cristiano; Maria Pastore, Gláucia (International Journal of Scientific World, 2016)
Worldwide oil production has been declining. Microbial enhanced oil recovery is one of the most important tertiary recovery processes. The aim of this work was to evaluate the surface activity properties of surfactin and mannosylerithritol lipids-B. In our previous studies, surfactin and mannosylerithritol lipids were produced using cassava wastewater as substrate and then purified by ultrafiltration. Thus, this work extends our previous studies. Experiments of surface activity under extreme conditions (temperature, ionic strength and pH), oil displacement, removal of oil from sand and emulsification index were carried out. Central composite rotational design was performed under extreme conditions of temperature, pH and ionic strength. The results indicated that ionic strength significantly affected the surface activity of surfactin. On the other hand, ionic strength, but also temperature and pH significantly affected the tenso activity of mannosylerithritol lipids-B. Regarding oil displacement test, mannosylerithritol lipids-B showed higher clear zone than surfactin. Contrary, in the experiments of removal of crude oil from sand, minimal differences were observed between surfactin and mannosylerithritol lipids-B. Therefore, both surfactin and mannosylerithritol lipids-B showed good surface activity under extreme conditions. In addition, it seems that mannosylerithritol lipids-B is subtly better than surfactin for microbial enhanced oil recovery.